The implications of demographic change and ageing for social protection in sub-Saharan Africa: insights from Rwanda. Issue 4 (1st October 2020) - Sabates-Wheeler, Rachel; Wylde, Emily; Aboderin, Isabella; Ulrichs, Martina
ABSTRACT: There has been minimal consideration of the implications of demographic and social shifts for future old-age social protection needs and programming in sub-Saharan Africa. In this paper we address this gap, building on the example of Rwanda. We utilise mixed-methods research to show that aggregate national statistics mask many of the complex vulnerabilities that older people face. These, combined with our projections of changes in Rwanda's economy, suggest an expanding unmet need for social protection among Rwanda's older population. A universal social pension is one affordable way to respond to this gap in provision both now and in the future.